2021
DOI: 10.1016/j.jot.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral tissue engineering: Perspectives for clinical application and preclinical development

Abstract: The treatment of osteochondral defects (OCD) remains challenging. Among currently available surgical treatments for OCDs, scaffold-based treatments are promising to regenerate the osteochondral unit. However, there is still no consensus regarding the clinical effectiveness of these scaffold-based therapies for OCDs. Previous reviews have described the gradient physiological characteristics of osteochondral tissue and gradient scaffold design for OCD, tissue engineering strategies, biomaterials, and fabrication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…First, a porous structure with a sufficient pore size to allow the exchange of bone cells, nutrients and metabolites. It is generally accepted that a pore size greater than 300 ​μm is suitable for the formation of blood vessels and new bone [ [37] , [38] , [39] , [40] ]. Second, there should be a surface that allows blood vessels to grow, bone cells to attach, migrate, and proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…First, a porous structure with a sufficient pore size to allow the exchange of bone cells, nutrients and metabolites. It is generally accepted that a pore size greater than 300 ​μm is suitable for the formation of blood vessels and new bone [ [37] , [38] , [39] , [40] ]. Second, there should be a surface that allows blood vessels to grow, bone cells to attach, migrate, and proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…Autograft osteochondral transfer (AOT) mosaicplasty, one of the most extensively applied surgical techniques in clinical practice, involves transplantation of multiple small cylindrical autologous osteochondral units as plugs from less load-bearing sites to the defect sites [ [1] , [2] , [3] ]. The operation offers several advantages over other repair techniques such as primary repair, less incision and injury, lower cost, and quick recovery [ [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated the enormous potential of biomaterials and tissue engineering strategies to totally or partially replace tissues or organs [ 12 ]. The choice of polymer is crucial in this regard as it should possess a high degree of modifiability for the specific application of interest [ 13 ].…”
Section: Introductionmentioning
confidence: 99%